JOINTING, STRESS-DEFORMATION STATE AND STRENGTH OF ELEMENTS OF WOODEN ROOFING STRUCTURES - Kadyrov Giyozjon Mirzajonovich (Western European Studies, 2025)
The article discusses methods for fastening elements of wooden roofing structures, their design features, advantages and disadvantages, as well as measures to improve seismic resistance.
Keywords: wooden joints; fasteners; bending; stretching